5-HT2C Receptors in the Pathophysiology of CNS Disease - Di Giovanni, Giuseppe; Esposito, Ennio; Di Matteo, Vincenzo; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2011)
Research of 5-HT2c receptors stretches back twenty-five years, and while much of it has been productive, the past decade of research has been extraordinary in terms of both amount produced and insights gained. It is hardly surprising that 5-HT2c receptor research has grown so fruitful, given that it is a prominent central serotonin receptor subtype widely expressed within the central and the peripheral nervous system and is thought to play a major role in the regulation of numerous behaviors. It has further been shown by experimental and clinical observation that it may represent a possible therapeutic target for the development of drugs for a range of central nervous system disorders. The time, therefore, is more than appropriate to offer the first ever overview of the research of 5-HT2c receptors. Part of the popular and important series, (3z(BThe Receptors,(3y (BThe 5-HT2c Receptor provides a thorough update of the functional status of the 5-HT2c receptor. It covers the molecular, cellular, anatomical, biochemical and behavioral aspects of this receptor so as to highlight its distinctive regulatory properties and the emerging functional significance of constitutive activity and RNA-editing in vivo. In addition, the book investigates the receptors$1 (Btherapeutic potential in a range of different diseases, treated individually in separate chapters, including depression, drug abuse, schizophrenia, eating disorders, Parkinson$1 (Bs disease, Prader-Willi Syndrome, Alzheimer$1 (Bs disease and epilepsy. While not exhaustive, this text is a vital tool in understanding the past and inspiring the future of interdisciplinary research on the 5-HT2c receptor.s
The making of the 5-HT2C receptor -- Serotonin 5-HT2C receptors: chemical neuronatomy in the mammalian brain -- The medicinal chemistry of 5-HT2C receptor ligands -- Insights into 5-HT2C receptor function gained from transgenic mouse models -- Serotonin 5-HT2C receptor signal transduction -- Homology modeling of 5-HT2C receptors -- 5-HT2C receptor dimerization -- RNA editing of 5-HT2C receptor and neuropsychiatric diseases -- Serotonergic control of adult neurogenesis: focus on 5-HT2C receptors -- The constitutive activity of 5-HT2C receptors as an additional modality of interaction of the serotonergic system -- The 5-HT2C receptor subtype controls central dopaminergic systems: evidence from electrophysiological and neurochemical studies -- The role of serotonin-2C receptors in the pathophysiology of depression -- 5-HT2C receptors and suicidal behaviour -- The 5-HT2C receptor as a target for schizophrenia -- Serotonin and reward-related behaviour: focus on 5-HT2C receptors -- Tat-3L4F: a novel peptide for treating drug addiction by disrupting interaction between PTEN and 5-HT2C receptor -- The role of serotonin in eating behaviour: focus on 5-HT2C receptors -- Physiological and pathophysiological aspects of 5-HT2C receptors in basal ganglia -- Modeling tardive dyskinesia: predictive 5-HT2C receptor antagonist treatment -- The role of 5-HT2A/2C receptors in sleep and waking -- Role of alternative splicing of the 5-HT2C in the Prader-Willi syndrome -- The role of 5-HT2C receptor in epilepsy -- The role of serotonin on attentional processes and executive functioning: focus on 5-HT2C receptors -- 5-HT2C receptors in learning -- The role of 5-HT2C polymorphisms in behavioural and psychological symptoms of alzheimer's disease -- Ocular hypotension: involvement of serotonergic 5-HT2C receptors.
Keywords: Medicine; Human physiology; Neurosciences; Toxicology; Neurology; Neurobiology; Biomedicine; Neurosciences; Pharmacology/Toxicology.; Human Physiology; Neurobiology; Neurology